Radially dependent effective piezoelectric coefficient and enhanced piezoelectric potential due to geometrical stress confinement in ZnO nanowires/nanotubes - Kim, S; Sohn, J; Kim, H; Ku, J; Park, Y; Cha, SN; Kim, J (2012)
A theoretical model for the radially dependent effective piezoelectric coefficient and corresponding piezoelectric potential in intrinsic ZnO nanowires (NWs)/nanotubes (NTs) is presented. Substrate-bound ZnO structures oriented along the c-axis with diameters of 100-5000 nm (NWs) and inner diameters of 100-900 nm (NTs; fixed outer diameter, 1000 nm) were examined using finite element method analysis. The piezoelectric potential depended nonlinearly on the NT/NW size, which we explain using the effective piezoelectric coefficient and peak piezoelectric potentials. We propose that this coefficient can be used to judge the degree of enhancement of the piezoelectric potential in ZnO NWs/NTs. © 2012 American Institute of Physics.